Controlling necking in extrusion film casting using polymer nanocomposites - Rokade, Dhammaraj; Azad, Lal B.; Poddar, Suparna; Mishra, Satyendra; Pol, Harshawardhan V.; Shukla, Rishab (Journal of Macromolecular Science Part B-Physics, 2017)
The research described was concerned with the effect of layered-silicate-based organically modified nanoclay fillers on controlling the extent of necking in a polymer melt extrusion film casting (EFC) process. We show that a linear polythylene resin (such as a linear low-density polyethylene-LLDPE) filled with a very low percentage of well-dispersed (or intercalated) nanoclay displays an enhanced resistance to the necking phenomenon. In general, melt-compounded nanoclay-filled LLDPE resin formulations displayed a higher final film width (less necking), thus a lower final film thickness (greater draw down for the same draw ratio), and cooled down faster when compared to the base LLDPE resin. Incorporation of nanoclay filler in the mainly linear chain LLDPE resin led to significant modification of the melt rheological properties that, in turn, affected the melt processability of these formulations. Primarily, the intercalated nanoclay-filled LLDPE formulations displayed the presence of strain-hardening in unaxial extensional rheology. Additionally, the presence of well-dispersed nanoclay in the LLDPE resin led to a display of prominent extrudate swell indicating the presence of melt elasticity in such formulations. The presence of melt elasticity, as shown by shear rheology and strain-hardening, observed by uniaxial extensional rheology, contributed to the LLDPE nanoclay formulations displaying an enhanced resistance to necking for these films. It can be concluded that linear chain polymers susceptible to necking in an EFC process can be made more resistant to such necking by using nanoclay fillers at very low levels of loading.

Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.